The Overexpressed MicroRNAs miRs-182, 155, 493, 454, and U6 snRNA and Underexpressed let-7c, miR-328, and miR-451a as Potential Biomarkers in Invasive Breast Cancer and Their Clinicopathological Significance - Záveský, Luděk; Jandáková, Eva; Weinberger, Vit; Minář, Luboš; Kohoutová, Milada; Tefr Faridová, Adela; Slanař, Ondřej (Oncology, 2025)
INTRODUCTION: Breast cancer comprises the leading cause of cancer-related death in women. MicroRNAs (miRNAs) have emerged as important factors with concern to carcinogenesis and have potential for use as biomarkers. METHODS: This study provides a comprehensive evaluation of the microRNA expression in invasive breast carcinoma of no special type tissues compared with benign tissues via large-scale screening and the candidate-specific validation of 15 miRNAs and U6 snRNA applying qPCR and the examination of clinicopathological data. RESULTS: Of the six downregulated miRNAs, let-7c was identified as the most promising miRNA biomarker and its lower expression was linked with Ki-67 positivity, luminal B versus luminal A samples, multifocality, lymph node metastasis, and inferior PFS. Of the 9 upregulated sncRNAs, the data on U6 snRNA, miR-493 and miR-454 highlighted their potential oncogenic functions. An elevated U6 snRNA expression was associated with the tumor grade, Ki-67 positivity, luminal B versus A samples, lymph node metastasis, and worsened PFS (and OS) outcomes. An elevated miR-454 expression was detected in higher grades, Ki-67 positive and luminal B versus A samples. Higher miR-493 levels were noted for the tumor stage (and grade) and worse patient outcomes (PFS, OS). The data also suggested that miR-451a and miR-328 may have tumor suppressor roles, and miR-182 and miR-200c pro-oncogenic functions, while the remaining sncRNAs did not evince any significant associations. CONCLUSION: We showed particular microRNAs and U6 snRNA as differentially expressed between tumors and benign tissues and associated with clinicopathological parameters, thus potentially corresponding with important roles in breast carcinogenesis. Their importance should be further investigated and evaluated in follow-up studies to reveal their potential in clinical practice. INTRODUCTION: Breast cancer comprises the leading cause of cancer-related death in women. MicroRNAs (miRNAs) have emerged as important factors with concern to carcinogenesis and have potential for use as biomarkers. METHODS: This study provides a comprehensive evaluation of the microRNA expression in invasive breast carcinoma of no special type tissues compared with benign tissues via large-scale screening and the candidate-specific validation of 15 miRNAs and U6 snRNA applying qPCR and the examination of clinicopathological data. RESULTS: Of the six downregulated miRNAs, let-7c was identified as the most promising miRNA biomarker and its lower expression was linked with Ki-67 positivity, luminal B versus luminal A samples, multifocality, lymph node metastasis, and inferior PFS. Of the 9 upregulated sncRNAs, the data on U6 snRNA, miR-493 and miR-454 highlighted their potential oncogenic functions. An elevated U6 snRNA expression was associated with the tumor grade, Ki-67 positivity, luminal B versus A samples, lymph node metastasis, and worsened PFS (and OS) outcomes. An elevated miR-454 expression was detected in higher grades, Ki-67 positive and luminal B versus A samples. Higher miR-493 levels were noted for the tumor stage (and grade) and worse patient outcomes (PFS, OS). The data also suggested that miR-451a and miR-328 may have tumor suppressor roles, and miR-182 and miR-200c pro-oncogenic functions, while the remaining sncRNAs did not evince any significant associations. CONCLUSION: We showed particular microRNAs and U6 snRNA as differentially expressed between tumors and benign tissues and associated with clinicopathological parameters, thus potentially corresponding with important roles in breast carcinogenesis. Their importance should be further investigated and evaluated in follow-up studies to reveal their potential in clinical practice.
Keywords: Female; lymfatické metastázy; lidé středního věku; miR-493; Breast Neoplasms; regulace genové exprese u nádorů; Breast cancer; RNA malá jaderná; nádory prsu; Biomarkers, Tumor; miR-328; invazivní růst nádoru; Humans; dospělí; miR-182; Prognosis; MicroRNAs; Neoplasm Invasiveness; nádorové biomarkery; miR-200c; let-7c; lidé; mikro RNA; Middle Aged; miR-454; senioři; miR-451a; prognóza; Lymphatic Metastasis; ženské pohlaví; U6 snRNA; MicroRNA; Aged; Gene Expression Regulation, Neoplastic; Adult; RNA, Small Nuclear